Chronic sleep restriction induces long-lasting changes in adenosine and noradrenaline receptor density in the rat brain - KIM, YOUNGSOO (J Sleep Res, 2015)
Although chronic sleep restriction frequently produces long-lasting behavioural and physiological impairments in humans, the underlying neural mechanisms are unknown. Here we used a rat model of chronic sleep restriction to investigate the role of brain adenosine and noradrenaline systems, known to regulate sleep and wakefulness, respectively. The density of adenosine A1 and A2a receptors and β-adrenergic receptors before, during and following 5 days of sleep restriction was assessed with autoradiography. Rats (n = 48) were sleep-deprived for 18 h day(–1) for 5 consecutive days (SR1–SR5), followed by 3 unrestricted recovery sleep days (R1–R3). Brains were collected at the beginning of the light period, which was immediately after the end of sleep deprivation on sleep restriction days. Chronic sleep restriction increased adenosine A1 receptor density significantly in nine of the 13 brain areas analysed with elevations also observed on R3 (+18 to +32%). In contrast, chronic sleep restriction reduced adenosine A2a receptor density significantly in one of the three brain areas analysed (olfactory tubercle which declined 26–31% from SR1 to R1). A decrease in b-adrenergic receptors density was seen in substantia innominata and ventral pallidum which remained reduced on R3, but no changes were found in the anterior cingulate cortex. These data suggest that chronic sleep restriction can induce long-term changes in the brain adenosine and noradrenaline receptors, which may underlie the long-lasting neurocognitive impairments observed in chronic sleep restriction.